Solid electrolyte and preparation method thereof, diaphragm, battery and power-related equipment
By adopting a solid electrolyte with a core-shell composite structure in lithium-ion batteries, the LATP core is combined with the Mg-Sn alloy shell, which solves the shortcomings in safety, stability and performance in lithium-ion battery technology and achieves higher battery performance and security.
Patent Information
- Application Number
- CN202510008474.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-03
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2045-01-03
AI Technical Summary
The existing lithium-ion battery technology has many defects in terms of safety, stability and performance. The safety risks of liquid electrolytes, the air instability of solid electrolytes, and the inadequate ionic conductivity and cycling stability have limited the lithium-ion battery to be more stable. Applications in a wide range of fields.
A solid electrolyte with a core-shell composite structure is adopted, with LATP as the core, and the outer layer is coated with the Mg-Sn alloy shell, and is prepared by ball milling, sintering and cooling processes to improve the air stability and ionic conductivity of the electrolyte.
It significantly improves the air stability, ionic conductivity, cycle stability and electrochemical windows of solid electrolytes, improves the charging and discharging efficiency and safety of the battery, and extends the service life of the battery.
Smart Images

Figure CN119400940A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium batteries, and in particular to a solid electrolyte and a preparation method thereof, a diaphragm, a battery and electrical equipment. Background Art
[0002] As a highly efficient energy storage device, lithium-ion batteries play an important role in modern electronic devices and electric vehicles. With the advancement of science and technology and the growth of energy demand, lithium-ion battery technology has become one of the key technologies in the field of new energy. However, as the scope of application expands, its safety and performance issues have gradually become the main bottleneck restricting its further development.
[0003] In the prior art, lithium-ion batteries mainly use organic liquid electrolytes, which have high ionic conductivity but poor chemical stability. These safety issues limit the application of lithium-ion batteries in extreme environments such as high temperature and high pressure, and also increase the complexity and cost of battery management systems.
[0004] In the research of solid electrolytes, garnet oxide solid electrolytes such as LATP have attracted attention due to their high ionic conductivity and good mechanical properties. However, LATP solid electrolytes have poor stability in the air and are easily reacted with water vapor, carbon dioxide, etc. to generate Li2CO3 impurities with low ionic conductivity. This reaction not only reduces the performance of the electrolyte, but may also cause damage to the internal structure of the battery, affecting the long-term stability and reliability of the battery.
[0005] In addition, the existing LATP solid electrolyte still needs to be improved in terms of ionic conductivity and cycle stability. The lack of ionic conductivity limits the battery's charge and discharge rate and power density, while the lack of cycle stability affects the battery's service life and performance retention. These problems are particularly prominent in high-power applications and long-cycle operations, and have become the main obstacles to the development of solid-state battery technology.
[0006] In summary, existing lithium-ion battery technology has many defects in terms of safety, stability and performance. The safety hazards of liquid electrolytes, the air instability of solid electrolytes, and the lack of ionic conductivity and cycle stability are the main challenges facing current lithium-ion battery technology. These defects limit the application of lithium-ion batteries in a wider range of fields and put forward higher requirements for their future technological development.
[0007] In view of this, the present invention is proposed. Summary of the invention
[0008] The object of the present invention is to provide a solid electrolyte and a preparation method, a diaphragm, a battery and electrical equipment. The solid electrolyte has good electrical and thermal conductivity, can improve the electrical conductivity of the battery, reduce the internal resistance of the battery, and thus improve the charging and discharging efficiency of the battery.
[0009] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted: In a first aspect, the present invention provides a solid electrolyte having a core-shell composite structure with LATP as a core and Mg-Sn alloy as a shell covering the outer surface of the core.
[0010] The LATP is Li y Al x Ti 2-x (PO4)3; where yx=1, 0<x<2, 1<y<3; The mass fraction of the Mg-Sn alloy in the solid electrolyte is 1% to 10%.
[0011] In an optional embodiment, in the LATP, yx=1, 0.5≤x<2, 1<y<3; and / or, the molar ratio of Mg to Sn in the Mg-Sn alloy is 1:4; and / or, the mass fraction of the Mg-Sn alloy in the solid electrolyte is 4%~10%.
[0012] In a second aspect, the present invention provides a method for preparing a solid electrolyte as described in any one of the aforementioned embodiments, comprising: The LATP and the Mg-Sn alloy are ball-milled together, and then sintered and cooled to obtain the solid electrolyte.
[0013] In an optional embodiment, the sintering process is to perform the following processing steps in sequence: A. Sinter in air at 200℃~250℃ for 1 hour~2 hours; B. Calcinate at 650℃~700℃ for 2 hours~4 hours; C. Sinter at 700℃~750℃ for 1 hour~2 hours.
[0014] In an optional embodiment, the method for preparing the Mg-Sn alloy includes: Mixing magnesium powder and tin powder to obtain a mixed powder; The mixed powder is subjected to ball milling, pressing and sintering to obtain the Mg-Sn alloy.
[0015] In an optional embodiment, the ball milling treatment time is 2 hours to 8 hours; and / or the pressure of the press molding treatment is 5t to 10t; and / or the sintering temperature of the sintering treatment is 200℃ to 400℃; and / or the sintering time of the sintering treatment is 4 hours to 12 hours.
[0016] In an optional embodiment, the method for preparing the LATP comprises: The lithium source, phosphorus source, aluminum source and titanium source are mixed according to a stoichiometric ratio in which the lithium source is in excess of 5% to 15%, a sintering aid is added, and the mixture is calcined to obtain the LATP.
[0017] In an optional embodiment, the lithium source includes: Li2CO3; and / or, the phosphorus source includes: (NH4)H2PO4; and / or, the aluminum source includes: Al2O3; and / or, the titanium source includes: TiO2; and / or, the sintering aid includes at least one of aluminum oxide, lithium tetrafluoroborate, tetrabutylammonium tetrafluoroborate and ammonium tetrafluoroborate; and / or, the mass fraction of the sintering aid is 1%~2%.
[0018] In a third aspect, the present invention provides a diaphragm, comprising the solid electrolyte as described in any one of the aforementioned embodiments; or, the solid electrolyte obtained by the preparation method of the solid electrolyte as described in any one of the aforementioned embodiments.
[0019] In a fourth aspect, the present invention provides a battery, comprising the separator as described in the above embodiment.
[0020] In a fifth aspect, the present invention provides an electrical device, comprising the battery as described in the above embodiment.
[0021] Compared with the prior art, the present invention has the following beneficial effects: The present invention proposes a solid electrolyte with a core-shell composite structure, in which LATP is used as the core and the outer layer is coated with a Mg-Sn alloy shell. This design significantly improves the air stability of the solid electrolyte, because the Mg-Sn alloy shell can effectively isolate water vapor and carbon dioxide in the air, prevent the LATP core from reacting with air, and thus avoid the generation of Li2CO3 impurities with low ionic conductivity. The high ionic conductivity of the Mg-Sn alloy is combined with the LATP core, which further improves the ionic conductivity of the overall electrolyte. At the same time, the shell can also inhibit the ion migration of the core, and enhance the structural and electrochemical performance stability of the electrolyte during the battery cycle. In addition, the wide electrochemical window of the LATP core is maintained, and the addition of the Mg-Sn alloy shell does not reduce its electrochemical window, ensuring that the electrolyte can maintain a wider electrochemical window. The combination of the high mechanical strength of the Mg-Sn alloy shell and the LATP core enhances the overall mechanical strength and impact resistance of the electrolyte. The excellent corrosion resistance, tear resistance and puncture resistance of the Mg-Sn alloy further improve the safety and stability of the battery system. The aluminum element in LATP promotes the formation of Mg2Sn phase and further improves the strength of Mg-Sn alloy, making this core-shell structured solid electrolyte show significant advantages in improving battery performance and safety. At the same time, its good electrical and thermal conductivity helps to improve the battery's electrical conductivity, reduce internal resistance, and improve the battery's charge and discharge efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0023] Figure 1 is a schematic diagram of the cross-sectional structure of the solid electrolyte particles in the embodiment of the present application; Figure 2 This is a schematic diagram of the results of the ionic conductivity and high temperature shrinkage rate in the test experiment 1 of this application; Figure 3 This is a schematic diagram of the results of the electrochemical performance investigation in test experiment 2 of this application.
[0024] Reference numerals: 100, solid electrolyte; 1, LATP; 2, Mg-Sn alloy. DETAILED DESCRIPTION
[0025] The embodiments of the present invention will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. If no specific conditions are specified in the examples, the conditions are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be obtained commercially.
[0026] refer to Figure 1 In the embodiment of the present application, a solid electrolyte is provided, wherein the solid electrolyte has a core-shell composite structure with LATP as the core and Mg-Sn alloy as the shell covering the outer surface of the core. The LATP is Li y Al x Ti 2-x (PO4)3; wherein yx=1, 0<x<2, 1<y<3; the mass fraction of the Mg-Sn alloy in the solid electrolyte is 1% to 10%. The mass fraction may be, for example, 1%, 2%, 4%, 6%, 8%, 10%, and the like.
[0027] It should be noted that LATP, as a Nasicon-type oxide solid electrolyte, has a high ionic conductivity (10 -4 S / cm) and good chemical stability. LATP shows good stability in humid air or carbon dioxide environment and has a high oxidation potential, which makes LATP an ideal solid electrolyte material for high-voltage solid-state batteries.
[0028] Mg-Sn alloy was selected as the shell material due to its good strength and hardness, and coated on the surface of LATP. This alloy not only improves the strength and durability of the diaphragm, but also enhances the safety and stability of the entire battery system due to its excellent corrosion resistance, tear resistance and puncture resistance. In addition, the electrical and thermal conductivity of Mg-Sn alloy helps to improve the conductivity of the battery and reduce the internal resistance of the battery, thereby improving the charge and discharge efficiency of the battery.
[0029] The adoption of the core-shell structure solves the problem of poor stability of LATP in the air. The Mg-Sn alloy shell effectively blocks water vapor and carbon dioxide in the air, preventing LATP from reacting with air to generate Li2CO3 impurities with low ionic conductivity, thereby improving the air stability of the solid electrolyte. At the same time, the high ionic conductivity of the Mg-Sn alloy is combined with the LATP core to improve the ionic conductivity of the overall solid electrolyte.
[0030] The Mg-Sn alloy shell can also inhibit the ion migration of the LATP core, improving the structural stability and electrochemical performance stability of the solid electrolyte during battery cycling. The LATP core has a wide electrochemical window, and the introduction of the Mg-Sn alloy shell does not reduce this characteristic, allowing the core-shell structure solid electrolyte to maintain a wide electrochemical window.
[0031] In summary, the solid electrolyte technology solution in the embodiment of the present application fully utilizes the core advantages of LATP through the design of the core-shell structure, and with the help of the characteristics of the Mg-Sn alloy shell, comprehensively improves the air stability, ionic conductivity, cycle stability and electrochemical window of the solid electrolyte, providing a high-performance solid electrolyte material for the development of all-solid-state batteries.
[0032] In addition, the role of aluminum in Mg-Sn alloy is to promote the formation of Mg2Sn phase. Mg2Sn is a precipitation phase in Mg-Sn alloy with excellent precipitation hardening effect. In the alloy, Sn and Mg form Mg2Sn phase, which is formed on the grain boundary and has a significant effect on improving the strength and hardness of the alloy. The addition of aluminum can improve the precipitation behavior of Mg2Sn phase in Mg-Sn alloy, thereby improving the precipitation hardening effect of the alloy.
[0033] The addition of aluminum to LATP can significantly improve the interfacial stability of Mg-Sn alloys. According to first-principles calculations, the doping of aluminum at the Mg(0001) / Mg2Sn(022) interface can reduce the interfacial energy and enhance the adhesion work of the interface. In particular, when aluminum atoms occupy specific doping positions, the strength of the Al-Sn bond at the interface dominates, which helps to improve the stability of the interface.
[0034] Aluminum can also refine the Mg2Sn phase, thereby improving the mechanical properties of the alloy. Experimental studies have shown that the addition of aluminum can significantly change the distribution and morphology of Mg2Sn, refine Mg2Sn, and improve the mechanical properties of Mg-Sn alloys.
[0035] The addition of aluminum improves the strength of Mg-Sn alloy. This is because the addition of aluminum can inhibit the coarsening of Mg2Sn phase and refine Mg2Sn, thereby improving the mechanical properties of the alloy. In addition, the solid solution strengthening effect of aluminum is also higher than that of other elements such as zinc (Zn), which can more effectively improve the yield strength and tensile strength of the alloy.
[0036] In summary, the aluminum element in LATP significantly improves the performance of Mg-Sn alloy by promoting the formation of Mg2Sn phase, enhancing interface stability, refining Mg2Sn phase and improving alloy strength. This strengthening effect is of great significance for improving the overall performance and stability of solid electrolytes.
[0037] In an alternative embodiment, the LATP chemical formula Li y Al x Ti 2-x The conditions satisfied by x and y in (PO4)3 are: yx=1, 0.5≤x<2, 1<y<3. In an optional embodiment, the molar ratio of Mg to Sn in the Mg-Sn alloy is 1:4.
[0038] In an optional embodiment, the mass fraction of the Mg-Sn alloy in the solid electrolyte is 4% to 10%, for example, 4%, 5%, 6%, 8%, 9%, 10%, etc.
[0039] In a second aspect, the present invention provides a method for preparing a solid electrolyte as described in any one of the aforementioned embodiments, comprising: The LATP and the Mg-Sn alloy are ball-milled together, and then sintered and cooled to obtain the solid electrolyte.
[0040] The present invention provides a method for preparing a solid electrolyte as described in the above embodiment, wherein the sintering process comprises the following steps: A. Sinter in air at 200°C to 250°C for 1 to 2 hours; for example, the sintering temperature can be 200°C, 220°C, 240°C, 250°C, etc.; the sintering time can be 1 hour, 1.5 hours, 2 hours, etc.
[0041] B. Calcinate at 650°C to 700°C for 2 to 4 hours; for example, the calcination temperature may be 650°C, 680°C, 690°C, 700°C, etc. The calcination time may be 2 hours, 3 hours, 4 hours, etc.
[0042] C. Sintering at 700°C to 750°C for 1 to 2 hours. For example, the sintering temperature may be 700°C, 720°C, 740°C, 750°C, etc.; the sintering time may be 1 hour, 1.5 hours, 2 hours, etc.
[0043] In an optional embodiment, the method for preparing the Mg-Sn alloy comprises: Mixing magnesium powder and tin powder to obtain a mixed powder; The mixed powder is subjected to ball milling, pressing and sintering to obtain the Mg-Sn alloy.
[0044] In an optional embodiment, when preparing the Mg-Sn alloy, the ball milling time is 2 hours to 8 hours; for example, the time can be 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, etc.
[0045] In an optional embodiment, when preparing the Mg—Sn alloy, the pressure of the press forming process is 5t~10t; for example, the pressure may be 5t, 6t, 7t, 8t, 10t, etc. In an optional embodiment, when preparing the Mg—Sn alloy, the sintering temperature of the sintering process is 200° C. to 400° C.; for example, the temperature may be 200° C., 300° C., 400° C., and the like.
[0046] In an optional embodiment, when preparing the Mg-Sn alloy, the sintering time of the sintering treatment is 4 hours to 12 hours. For example, the sintering time can be 4 hours, 5 hours, 6 hours, 7 hours, 9 hours, 10 hours, 12 hours, etc.
[0047] The mass fraction of the Mg-Sn alloy is 1% to 5%. For example, the mass fraction may be 1%, 3%, 4%, 5%, etc.
[0048] In an optional embodiment, the preparation method of the LATP comprises: The lithium source, phosphorus source, aluminum source and titanium source are mixed according to a stoichiometric ratio in which the lithium source is in excess of 5% to 15%, a sintering aid is added, and the mixture is calcined to obtain the LATP.
[0049] As mentioned above, in the process of preparing LATP (lithium aluminum titanium phosphate) solid electrolyte, excessive addition of lithium source, such as lithium carbonate, is mainly to compensate for the loss of lithium element during high-temperature calcination. As an active alkali metal element, lithium is easily volatilized at high temperatures, resulting in insufficient lithium content in the final product. In order to ensure the accurate stoichiometric ratio of lithium in the LATP material and obtain the ideal chemical composition and crystal structure, it is necessary to add an excessive amount of lithium source to the starting raw material to compensate for this loss. In addition, excessive lithium source can also improve the accuracy of the stoichiometric ratio and improve the conductivity and other physical properties of the electrolyte. When preparing LATP by solid phase method, if the lithium source is insufficient, impurity phases such as AlPO4 and TiO2 may be generated, which will reduce the ionic conductivity of the electrolyte. Therefore, excessive addition of lithium source helps to reduce the formation of these impurity phases and improve the performance of the electrolyte. In general, excessive addition of lithium source is to ensure the chemical stability and electrochemical performance of the LATP electrolyte, which is crucial to improving the efficiency, safety and cycle life of the battery.
[0050] In an optional embodiment, the lithium source includes: Li2CO3. In an optional embodiment, the aluminum source includes: Al2O3.
[0051] In an optional embodiment, the titanium source includes: TiO2. In an optional embodiment, the phosphorus source includes: (NH4)H2PO4. In an optional embodiment, the sintering aid includes at least one of aluminum oxide, lithium tetrafluoroborate, tetrabutylammonium tetrafluoroborate and ammonium tetrafluoroborate.
[0052] In an optional embodiment, the mass fraction of the sintering aid is 1% to 2%. For example, it can be 1%, 1.5%, 2%, etc.
[0053] A diaphragm is provided in an embodiment of the present application, comprising the solid electrolyte as described in any one of the aforementioned embodiments; or the solid electrolyte obtained by the preparation method of the solid electrolyte as described in any one of the aforementioned embodiments.
[0054] A battery is provided in an embodiment of the present application, comprising the separator as described in the above embodiment.
[0055] Accordingly, the present application also provides a method for preparing the above-mentioned diaphragm, which may include the following steps: melt-extruding the polyolefin and the above-mentioned solid electrolyte to obtain a cast sheet; stretching the cast sheet to obtain a stretched film; and winding and slitting the stretched film to obtain a diaphragm.
[0056] In the preparation process of the above-mentioned diaphragm, the weight of the solid electrolyte material is less than the weight of the polyolefin. That is, the weight ratio of the solid electrolyte to the polyolefin is less than 50:50, such as 49:51, 40:60, 30:70, 20:80, 10:90, etc.
[0057] In some embodiments, the average particle size of the solid electrolyte is ≤1 μm, such as 1 μm, 0.8 μm, 0.6 μm, 0.5 μm or 0.2 μm.
[0058] In some embodiments, the weight average molecular weight of the polyolefin can be 100,000 to 5 million, such as 100,000, 500,000, 1 million, 2 million, 3 million, 4 million, or 5 million.
[0059] In addition, the equipment used in each step of the above-mentioned membrane and other preparation conditions (for example, the preparation raw materials also include pore formers, the selection and dosage of pore formers, stretching parameters, etc.) can all refer to the existing technology and will not be elaborated here.
[0060] Furthermore, an electrical device is provided in an embodiment of the present application, including a battery as described in the aforementioned embodiment, which contains the above-mentioned diaphragm.
[0061] The battery has the advantages of high safety, excellent low-temperature rate charging and discharging capabilities, no lithium precipitation during low-temperature charging, and high constant current ratio during low-temperature charging.
[0062] Table 1. Main components and parameters of solid electrolytes in Examples and Comparative Examples
[0063] In the above table, Mg-4Sn alloy represents a Mg-Sn alloy in which the molar ratio of Mg to Sn is 1:4, and the same applies below.
[0064] Example 1 In this embodiment, a solid electrolyte was prepared. The solid electrolyte is Li 1.1 Al 0.2 Ti 1.8 The core-shell composite structure is composed of (PO4)3 as the core and Mg-4Sn alloy as the shell covering the outer surface of the core. 1.1 Al 0.2 Ti 1.8 (PO4)3@Mg-4Sn, the preparation method thereof is as follows: (1) Preparation of shell material: magnesium powder and tin powder were ball-milled at a molar ratio of 1:4 for 2 h, pressed under a pressure of 5 t and then sintered at a temperature of 200 °C for 4 h to generate Mg-4Sn alloy.
[0065] (2) Preparation of LATP: Lithium carbonate, ammonium hydrogen phosphate, titanium dioxide, and aluminum oxide were mixed according to Li 1.1 Al 0.2 Ti 1.8 The stoichiometric ratio of (PO4)3 was prepared, wherein lithium carbonate was added in an excess of 5% of the stoichiometric ratio, and 1% of tetrabutylammonium tetrafluoroborate was added and then calcined to obtain LATP [Li 1.1 Al 0.2 Ti 1.8 (PO4)3]; wherein the calcination temperature is 600°C and the calcination time is 1 h.
[0066] (3) Preparation of solid electrolyte LATP[Li 1.1 Al 0.2 Ti 1.8 (PO4)3] was ball-milled with 1% by mass Mg-4Sn alloy and then sintered in three stages, the first stage was sintered at 200°C for 1 h, the second stage was sintered at 650°C for 2 h, and the third stage was sintered at 700°C for 1 h, and then cooled to obtain a solid electrolyte.
[0067] (4) Preparing a diaphragm: melt-extrude the solid electrolyte and polyolefin (PP) to obtain a cast sheet; stretch the cast sheet to obtain a stretched film; and roll and slit the stretched film to obtain a diaphragm.
[0068] Example 2 In this example, a solid electrolyte was prepared. The preparation method used in this example is basically the same as that in Example 1, with the following differences (specific components and parameters can be found in Table 1): Li 1.1 Al 0.2 Ti 1.8 (PO4)3 replaced by Li 1.1 Al 0.3 Ti 1.7 (PO4)3, replacing the mass fraction of Mg-4Sn alloy with 2% Example 3 In this example, a solid electrolyte was prepared. The preparation method used in this example is basically the same as that in Example 1, with the following differences (specific components and parameters can be found in Table 1): Li 1.1 Al 0.2 Ti 1.8 (PO4)3 replaced by Li 1.1 Al 0.4 Ti 1.6 (PO4)3, replacing the mass fraction of Mg-4Sn alloy with 3% Example 4 In this example, a solid electrolyte was prepared. The preparation method used in this example is basically the same as that in Example 1, with the following differences (specific components and parameters can be found in Table 1): Li 1.1 Al 0.2 Ti 1.8 (PO4)3 replaced by Li 1.1 Al 0.5 Ti 1.5 (PO4)3, replacing the mass fraction of Mg-4Sn alloy with 4% Example 5 In this example, a solid electrolyte was prepared. The preparation method used in this example is basically the same as that in Example 1, with the following differences (specific components and parameters can be found in Table 1): Li 1.1 Al 0.2 Ti 1.8 (PO4)3 replaced by Li 1.1 Al 0.6 Ti 1.4 (PO4)3, replacing the mass fraction of Mg-4Sn alloy with 5% Example 6 In this example, a solid electrolyte was prepared. The preparation method used in this example is basically the same as that in Example 1, with the following differences (specific components and parameters can be found in Table 1): Li1.1 Al 0.2 Ti 1.8 (PO4)3 replaced by Li 1.3 Al 0.5 Ti 1.4 (PO4)3, replacing the mass fraction of Mg-4Sn alloy with 4% Example 7 In this example, a solid electrolyte was prepared. The preparation method used in this example is basically the same as that in Example 1, with the following differences (specific components and parameters can be found in Table 1): Li 1.1 Al 0.2 Ti 1.8 (PO4)3 replaced by Li 1.3 Al 0.5 Ti 1.5 (PO4)3, replacing the mass fraction of Mg-4Sn alloy with 5% Comparative Example 1 In this comparative example, a solid electrolyte was prepared. The preparation method used in this comparative example is basically the same as that in Example 1, with the following differences (specific components and parameters can be referred to Table 1): No Mg-4Sn alloy coating is used. That is, step (1) is not performed, and LATP is directly used as the solid electrolyte, and then the preparation of the diaphragm in step (4) is directly performed to obtain the diaphragm.
[0069] Horizontal test experiment: 1. Test experiment 1: Investigation of ionic conductivity and high temperature shrinkage.
[0070] A. Test method: (1) Ionic conductivity: The solid electrolyte prepared in Examples 1-7 and Comparative Example 1 was pressed into a solid electrolyte membrane (diaphragm), and then the solid electrolyte membrane was cut into discs with a diameter of 19 mm. The discs were sandwiched between two stainless steel gaskets to assemble a symmetrical battery; then the electrochemical workstation was connected and an impedance test was performed at room temperature of 25°C to obtain the bulk impedance value of the sample to be tested. The ionic conductivity was calculated according to the formula σ = L / (A×Rb), where σ is the ionic conductivity, in units of S / cm; L is the thickness of the pressed sheet, in units of cm; and A is the area of the pressed sheet, in units of cm 2 ; Rb is the body impedance of the sample to be tested, in Ω. Where L is 0.015cm, A is 2.84cm 2 .
[0071] (2) High temperature shrinkage rate: The diaphragms prepared in the above examples and the diaphragms listed in the comparative examples were cut into samples with a size of 10 cm × 10 cm, and the longitudinal length l of each sample was recorded. 原始, placed at 130 ℃ for 10 h, and the longitudinal length l of each sample was tested 保温 , calculate the shrinkage rate, shrinkage rate = (l 保温 / l 原始 )×100%.
[0072] B. Experimental results and analysis: Table 2. Transverse test results of the embodiments and comparative examples
[0073] (1) Refer to the experimental results in Table 2 and Figure 2 The ionic conductivity of Examples 1 to 7 is all within 9.0×10 −4 ~9.6×10 −4 S / cm range, showing relatively close ionic conductivity values, which indicates that the solid electrolyte and the diaphragm obtained by the method in the present application can achieve higher ionic conductivity, and the influence of different Mg-4Sn alloy mass fractions and LATP composition ratios on ionic conductivity is small.
[0074] (2) The ionic conductivity of comparative example 1 (without Mg-4Sn alloy coating) is the lowest, which is 5.5×10 −4 S / cm, which is significantly lower than that of all the embodiments, indicating that the addition of Mg-4Sn alloy significantly improves the ionic conductivity of the solid electrolyte.
[0075] (3) The high temperature shrinkage rates of Examples 1 to 7 are all between 4.2% and 4.5%, showing good thermal stability.
[0076] (4) The high-temperature shrinkage rate of Comparative Example 1 is 7.1%, which is higher than that of all the examples, indicating that the addition of Mg-4Sn alloy helps to significantly reduce the shrinkage rate of the solid electrolyte at high temperature, thereby improving its thermal stability.
[0077] 2. Test experiment 2: investigation of electrochemical performance.
[0078] A. Preparation and testing methods: The separators obtained in Example 1, Example 4, Example 5, Example 6, and Example 7 were made into batteries, and then the electrochemical performance was investigated. The specific method includes: (1) Adding the binder PVDF to NMP at a mass ratio of 1:8 and stirring to obtain a glue solution, then mixing the commercially available 8-series nickel-cobalt-manganese lithium ternary TLP813 material, the conductive agent acetylene black, and the glue solution at a mass ratio of 97:1:2, and stirring until the system is uniform under the action of a vacuum mixer to obtain a positive electrode slurry; (2) The positive electrode slurry is evenly coated on the positive electrode current collector, dried at room temperature and then transferred to an oven for further drying. The positive electrode sheets are then cold pressed and cut into pieces according to the required specifications.
[0079] (3) Mixing the negative electrode active material graphite, the conductive agent acetylene black, the thickener CMC, and the binder SBR in a mass ratio of 96.2:0.8:1.2:1.8, then adding deionized water as a solvent to the mixture, stirring the mixture under the action of a vacuum stirrer until the system becomes uniform, and obtaining a negative electrode slurry; (4) The negative electrode slurry is evenly coated on the negative electrode current collector, dried at room temperature, and then transferred to an oven for further drying. The negative electrode sheets are then cold pressed and cut into pieces according to the required specifications.
[0080] (5) The positive electrode sheet, the separator (the separator prepared in Example 1, Example 4, Example 5, Example 6 and Example 7), and the negative electrode sheet are stacked in order to obtain a battery cell after assembly.
[0081] (6) Place the battery cell assembly into the inner cavity of the battery shell, and after drying, inject electrolyte into the inner cavity of the battery shell. The electrolyte solvent is ethylene carbonate and the solute is lithium hexafluorophosphate (1 mol / L). After sealing, standing, forming, and volume separation, a square lithium-ion battery is obtained. The square battery has a capacity of 20Ah, a thickness of 15mm, a width of 119mm, and a height of 208mm.
[0082] (7) The retention rate of each square lithium-ion battery [1500 cycles at room temperature (25±5)℃] was tested.
[0083] B. Experimental results and analysis: Table 3. Retention rate of square lithium-ion batteries in the examples
[0084] (1) Refer to the retention test results in Table 3 and Figure 3 It can be seen that the cycle retention rate of Example 1 is 88.72%, which is relatively low. The cycle retention rates of Examples 4 to 7 all exceed 90%, among which the cycle retention rate of Example 7 is the highest, which is 91.39%.
[0085] (2) Examples 4 to 7 show higher cycle retention rates than Example 1, which indicates that when the mass fraction of Mg-4Sn alloy increases to 4% or above (mass fraction ≥ 4%) and the value of x in LATP satisfies 0.5≤x<2, the cycle performance of the battery is significantly improved, indicating that the addition of Mg-Sn alloy (Mg-4Sn) and the optimization of the specific LATP composition ratio are helpful to improve the battery performance.
[0086] (3) The core-shell structured solid electrolyte in the embodiment exhibits excellent battery cycling performance. The core-shell structure design utilizes the core advantages of LATP and, with the help of the characteristics of the Mg-4Sn alloy shell, comprehensively improves the air stability, ionic conductivity, cycling stability and electrochemical window of the solid electrolyte.
[0087] (4) The cycle retention rate of Example 7 is higher than that of Example 1. The data support that the aluminum element in the Mg-4Sn alloy promotes the formation of the Mg2Sn phase, further improving the strength of the Mg-4Sn alloy, making the core-shell structure solid electrolyte show significant advantages in improving battery performance. At the same time, good electrical and thermal conductivity helps to improve the electrical conductivity of the battery, reduce internal resistance, and improve the charge and discharge efficiency of the battery.
[0088] (5) The excellent corrosion resistance, tear resistance and puncture resistance of Mg-4Sn alloy further improve the safety and stability of the battery system.
[0089] In summary, based on the test results, this application can improve the ionic conductivity, cycle stability and electrochemical window of the solid electrolyte through the core-shell structure design and the application of Mg-Sn alloy, thereby improving the cycle retention rate and overall performance of the battery. These improvements provide a high-performance solid electrolyte material for the development of all-solid-state batteries, which helps to promote the advancement of lithium battery technology.
[0090] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A solid electrolyte, characterized in that The solid electrolyte has a core-shell composite structure with LATP as the core and Mg-Sn alloy as the shell covering the outer surface of the core; The LATP is Li y Al x Ti 2-x (PO4)3; where yx=1, 0<x<2, 1<y<3; The mass fraction of the Mg-Sn alloy in the solid electrolyte is 1% to 10%.
2. The solid electrolyte according to claim 1, characterized in that In the LATP, yx=1, 0.5≤x<2, 1<y<3; and / or, The molar ratio of Mg to Sn in the Mg-Sn alloy is 1:4; and / or, The mass fraction of the Mg-Sn alloy in the solid electrolyte is 4% to 10%.
3. A method for preparing a solid electrolyte according to any one of claims 1 to 2, characterized in that: include: The LATP and the Mg-Sn alloy are ball-milled together, and then sintered and cooled to obtain the solid electrolyte.
4. The method for preparing a solid electrolyte according to claim 3, characterized in that: The sintering process comprises the following steps: A. Sinter in air at 200℃~250℃ for 1 hour~2 hours; B. Calcinate at 650℃~700℃ for 2 hours~4 hours; C. Sinter at 700℃~750℃ for 1 hour~2 hours.
5. The method for preparing a solid electrolyte according to claim 3, characterized in that: The preparation method of the Mg-Sn alloy comprises: Mixing magnesium powder and tin powder to obtain a mixed powder; The mixed powder is subjected to ball milling, pressing and sintering to obtain the Mg-Sn alloy.
6. The method for preparing a solid electrolyte according to claim 5, characterized in that: The ball milling time is 2 hours to 8 hours; and / or, The pressure of the press forming process is 5t~10t; and / or, The sintering temperature of the sintering treatment is 200°C to 400°C; and / or, The sintering time of the sintering treatment is 4 hours to 12 hours.
7. The method for preparing a solid electrolyte according to claim 3, characterized in that: The preparation method of the LATP comprises: The lithium source, phosphorus source, aluminum source and titanium source are mixed according to a stoichiometric ratio in which the lithium source is in excess of 5% to 15%, a sintering aid is added, and the mixture is calcined to obtain the LATP.
8. The method for preparing a solid electrolyte according to claim 7, characterized in that: The lithium source includes: Li2CO3; and / or, The aluminum source includes: Al2O3; and / or, The titanium source comprises: TiO2; and / or, The phosphorus source includes: (NH4)H2PO4; and / or, The sintering aid comprises at least one of alumina, lithium tetrafluoroborate, tetrabutylammonium tetrafluoroborate and ammonium tetrafluoroborate; and / or, The mass fraction of the sintering aid is 1% to 2%.
9. A diaphragm, characterized in that: The invention comprises the solid electrolyte as claimed in any one of claims 1 to 2; or, comprises the solid electrolyte obtained by the preparation method of the solid electrolyte as claimed in any one of claims 3 to 8.
10. A battery, characterized in that: Comprising the diaphragm as claimed in claim 9.
11. An electrical equipment, characterized in that: Comprising the battery as claimed in claim 10.
Citation Information
Patent Citations
Solid electrolyte, preparation method thereof and lithium ion battery
CN106299468A
Solid electrolyte, preparation method thereof, all-solid-state lithium ion battery and manufacturing method of all-solid-state lithium ion battery
CN112768758A
Flexible solid electrolyte, all-solid-state lithium battery including the flexible solid electrolyte, and method of preparing the flexible solid electrolyte
US20140170504A1
Metal alloy layers on substrates, methods of making same, and uses thereof
US20190088986A1
Surface coatings for ceramic electrolyte particles
US20190123384A1
Cited By
Preparation method of lithium tin phosphorus sulfur solid-state battery
CN120341399A
Composite electrolyte material with lithium aluminum germanium phosphate core coated with metal organic framework shell layer and application of composite electrolyte material
CN122051398A